2001
DOI: 10.1161/hq0801.093669
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory Enlargement and Stenosis Develop in ApoE −/− and ApoE*3-Leiden Transgenic Mice

Abstract: Abstract-Atherosclerotic mouse models develop little ischemic organ damage and no infarctions, despite the presence of large atherosclerotic lesions. Therefore, we hypothesize that luminal changes do not follow atherosclerotic lesion development. Because a phenomenon that may explain the discrepancy between luminal changes and lesion size is vascular remodeling, we measured parameters of vascular remodeling in the carotid arteries (CAs), thoracic aorta (TA), and abdominal aorta (AA) of apolipoprotein E (apoE)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 62 publications
3
16
0
Order By: Relevance
“…The occurrence of remodeling in the aorta and carotid arteries of ApoE Ϫ/Ϫ mice has been reported previously (Lutgens et al, 2001;Choudhury et al, 2002). The present study confirms this earlier observation and, for the first time, provides information on the temporal relationship between atherosclerosis and remodeling.…”
Section: Discussionsupporting
confidence: 92%
“…The occurrence of remodeling in the aorta and carotid arteries of ApoE Ϫ/Ϫ mice has been reported previously (Lutgens et al, 2001;Choudhury et al, 2002). The present study confirms this earlier observation and, for the first time, provides information on the temporal relationship between atherosclerosis and remodeling.…”
Section: Discussionsupporting
confidence: 92%
“…1,7,21 Several lines of evidence implicate MMP as key effectors of this process. Pasterkamp et al reported increased levels of MMP-2 and MMP-9 in expansively remodeled segments of human coronary arteries compared with constrictively remodeled segments.…”
Section: Discussionmentioning
confidence: 99%
“…In apoE*3 Leiden and apoE knockout mice, lesion development was found associated with expansive arterial enlargement, medial thinning, and increased elastolytical activity. 41,67 These and other mouse model studies are rather descriptive, and the mechanistic link between atherosclerotic expansive remodeling and matrix degrading properties is therefore strongly suggested but yet unproven. Interventional studies using MMP inhibitors or atherosclerotic prone/protease double-knockout mice, similar to those performed in experimental models of aortic aneurysm, will be necessary.…”
Section: Expansive Atherosclerotic Remodeling: What Did We Learn Frommentioning
confidence: 99%